Combatting Plagiarism Using a Community of Practice Approach - Morton McKay, Tracey Jill (South African Journal of Higher Education, 2018)
A teaching intervention, informed by a community of practice approach, undertaken to manage a plagiarism problem is described. In particular, many final year students were submitting assignments that were, to a large extent, plagiarized. As this was a threat to the academic integrity of the academic programme, an intervention was necessary. A prevention-and-development approach was adopted as an operational practice. The intervention took the form of an action research project using critical reflection as a methodology. The intervention, especially phase two, was successful, although incidents of plagiarism were reduced, not completely eliminated. The teaching intervention proved to be both time and labour intensive. The intervention demonstrates that formal training for students on what plagiarism is, how to correctly cite and reference, and how to write in an academically appropriate manner, is necessary if plagiarism in higher education is to be dealt with within a developmental framework. It was further found that a prevention-and-development approach cannot be implemented without a detection-and-enforcement system being in place. Key words: plagiarism; academic literacy; community of practice; intervention; action research